Building a People-Oriented Security Community the ASEAN way. - Collins, Alan (Routledge contemporary Southeast Asia series., 2012)
ASEAN has declared its intention to create a security community in Southeast Asia that is people-orientated. This book evaluates ASEAN's progress, and in doing so examines three matters of concern. The book firstly looks at the importance of constitutive norms to the workings of security communities, by identifying ASEAN's constitutive norms and the extent to which they act as a help of hindrance in establishing a security community. It then moves on to how ASEAN has interpreted people-orientated as empowering civil society organisations to be community stakeholders. The book discuss.